(The Effect of the Mixed Flour to The Quality to Chiken Nugget) - Susanto, Eko; Lestari, Nami; Isyanti, Mirna; Rahardjo, Sumadyo (Balai Besar Industri Agro, 2011)
The studies Nugget is a product which can be produced from maced from chiken or fish with some ingredient and filler ,eventhoughnugget can be produsced whithout filler .in this research was carried out by adding wheat flour mixed with cassava based products i.e .mokaf ,tapioca and cassava flour.the result showed that by adding fillerÂ do not affect the organoleptic test such as taste ,colour ,texture and odour but the treatments was affect the nugget quality .the best quality of nugget was produced with addition of mixed filler from 25% wheat flour and 75% mokaf .the product has 15% protein ,12,9% fat and 27,7% carbohydrate .it is meet the requirement of SNI 01-6683-2002 for chicken nugget .